Fabrication of Latex-based Nanofibers by Electrospinning - Zhou, Chan-Juan; Chen, Chen; Zhou, Hong-yu; He, Ji-Huan (Recent Patents on Nanotechnology, 2019)
Background: Natural latex has been widely used in medical gloves, gas masks and nipples characterized by high elasticity, good film-forming performance and flexible film, but it is seldom used in nanomaterials. Electrospinning is an effective technology for manufacturing microfibrous or nanofibrous membranes. Latex-based nanofibers can be fabricated by electrospinning. Few relevant patents to the topic have been reviewed and cited. Methods: The natural rubber latex and PVA solution were prepared for electrospinning in this study. Results: When the rubber tends to nano scales, the flexibility of natural rubber gets enhanced. Additionally, the latex fluid can be used as an additive to improve mechanical property of nanofibers. Conclusion: The electrospinning rubber nanofibers shed a new light on rubber industry.
Keywords: mechanical property